THE EFFECTIVENESS OF COMIC STRIPS USE TOWARDS READING SKILL OF THE SEVENTH GRADE STUDENTS OF SMP N 9 YOGYAKARTA IN THE ACADEMIC YEAR 2016/2017 - Arifiana Tri Wulandari; Soviyah Soviyah (UAD TEFL International Conference)
Teaching method is one of the aspects that must be given attention in a teaching learning process. The use of media becomes important strategy to get success in teaching learning process especially in teaching reading. The use of comic strips in teaching reading is expected to increase the students’ achievement in reading. The aim of this research is to find out the effectiveness of comic strips in reading skill for students at the seventh grade of SMP N 9 Yogyakarta.This research is an experimental research. This research was conducted in the SMP N 9 Yogyakarta on 5th May until 19th May, 2017. The population of this research was the seventh grade students, and the samples of this research were 7B as the control class and 7C as the experimental class. The analysis technique used was quantitative. The instrument used in this research was pretest and posttest. The researcher used SPSS to analyze and calculate the data and to test the hypothesis.      The result of the calculation is to > ttable, it means that the Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted. The mean of the pretest was 52.80, and the mean of the posttest was 75.45. Based on the result of this research, it showed that the use of comic strips in teaching reading was effective.